2015
DOI: 10.1080/09540121.2015.1036725
|View full text |Cite
|
Sign up to set email alerts
|

Food insufficiency, housing and health-related quality of life: results from the Positive Spaces, Healthy Places study

Abstract: Studies of people living with HIV who are homeless or unstably housed show a high prevalence of food insufficiency (>50%) and associated poor health outcomes; however, most evidence is in the form of cross-sectional studies. To better understand this issue, we conducted a longitudinal study to examine the impact of food insufficiency and housing instability on overall physical and mental health-related quality of life (HRQoL) among people living with HIV in Ontario. Six hundred and two adults living with HIV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…Literature reviews of adults with HIV indicate that they face many challenges associated with health and well-being. These challenges encompass socioeconomics [ 5 , 6 ], depression [ 7 ], housing [ 8 ] and food security [ 9 , 10 ]. Older adults with HIV experience similar challenges [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature reviews of adults with HIV indicate that they face many challenges associated with health and well-being. These challenges encompass socioeconomics [ 5 , 6 ], depression [ 7 ], housing [ 8 ] and food security [ 9 , 10 ]. Older adults with HIV experience similar challenges [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, age-speci c physical health strengthening activities for adults over 25 years of age improve physical HRQoL. Faith-based behavioural and physical intervention strategies improve religious determinants of poor physical HRQoL, and tackling the issue of unemployment and food insecurity improves the physical HRQoL [42,40,50]. In addition, addressing social inequality brought about by unemployment, food insecurity and poor asset possession can enhance mental HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that unemployed PLWHAs are nearly twice more likely to have poor PHS scores. Likewise, it has been shown that unemployment leads to poor QoL among PLWHA in both developed and developing countries [13,18,50]. A study in Ethiopia has found that unemployed PLWHA are twice as likely to have poor physical HRQoL than employed PLWHA [23].…”
Section: Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…Research in the United States and Canada has identified similar impacts related to food insecurity (12−14). People with HIV who are food insecure are less likely to have undetectable viral loads and have higher morbidity and mortality, and poorer physical and mental health-related quality of life (15). They miss more primary care appointments and make less use of HIV treatment.…”
Section: The Impact Of Syndemicsmentioning
confidence: 99%